2021
DOI: 10.1002/micr.30809
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled anterolateral thigh flap transfer for the reconstruction of a large gluteal defect assisted by preoperative computed tomographic angiography and intraoperative indocyanine green angiography: A case report

Abstract: The efficacy of the use of the pedicled ALT flap for buttock defects has not been established in the literature. Here, we present a case of a successful reconstruction of a large gluteal defect after sarcoma resection using a pedicled ALT flap assisted by preoperative computed tomographic angiography (CTA) and intraoperative indocyanine green (ICG) angiography. A 94-year-old man underwent resection of a large soft tissue tumor in the gluteal region resulting in a 19 Â 15 cm defect. Based on three-dimensional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…While smaller defects can be addressed with primary closure, larger ones necessitate more advanced plastic and reconstructive surgery techniques, such as local or free flap transfers. These reconstruction techniques have been explored extensively in the academic literature [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. With the current improvements in microsurgical techniques and instruments, some recent studies have shown that free flap transfers have a similar safety profile to the reconstruction using a local flap [ 2 , 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While smaller defects can be addressed with primary closure, larger ones necessitate more advanced plastic and reconstructive surgery techniques, such as local or free flap transfers. These reconstruction techniques have been explored extensively in the academic literature [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. With the current improvements in microsurgical techniques and instruments, some recent studies have shown that free flap transfers have a similar safety profile to the reconstruction using a local flap [ 2 , 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In reconstructive microsurgery, ICG fluorescence angiography is mostly used for its predictive qualities regarding skin and flap survival. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] By distinguishing between well-perfused and poorly perfused tissues, ICG fluorescence angiography is fundamental for intraoperative decisionmaking and allows precise tailoring in view of minimal postoperative complications. [19][20][21][22] Because of real-time flow assessment, ICG fluorescence angiography is an accurate modality which has contributed to our understanding of flap dynamics and which is superior to the trained eye of the reconstructive surgeon.…”
mentioning
confidence: 99%